Analysis Of The Influence Of Service Quality And Trust On Customer Loyalty With Customer Satisfaction As Intervening Variable In Menantea Field - Ramadhan, Hafiz; Ronny Edward, Yusuf; Ariesa, Yeni (CV. Inara, 2022)
This study aims to analyze the effect of service quality on customer loyalty Menantea Medan, analyze the effect of trust on customer loyalty, analyze the effect of customer satisfaction on customer loyalty, analyze the effect of service quality on customer satisfaction, analyze the effect of trust on customer satisfaction, analyze the effect of service quality on customer loyalty. through customer satisfaction and analyze the effect of trust on customer loyalty through customer satisfaction Menantea Medan. This research is a quantitative descriptive with a questionnaire instrument with a population of all regular customers of Menantea Medan for the 2021 period as many as 5,859 people, the determination of the sample using an accidental sample is achieved by the research sample as many as 155 people. The results showed that the RSquare value was 0.551 or R2 x 100% of 55.10%, meaning that the service quality and trust variables made a major contribution to explaining customer loyalty by 55.10%, the remaining 44.90% were other factors and the RSquare value was 0.850 or R2 x 100% is 85.50%, meaning that the service quality and trust variables contribute in explaining customer loyalty by 85.00%, the remaining 15.00% is another factor. The conclusion of the study is that service quality has a significant effect on customer loyalty, Menantea Medan, trust has a significant effect on customer loyalty, customer satisfaction has a significant effect on customer loyalty, and service quality has a significant effect on customer satisfaction. trust has a significant effect on customer satisfaction, service quality has a significant effect on customer loyalty through customer satisfaction and trust has no effect on customer loyalty through customer satisfaction Menantea Medan.